2018
DOI: 10.1590/1678-7757-2017-0115
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of calcium silicate-based formulations MTA Repair HP and MTA Vitalcem

Abstract: ObjectiveThis study aimed to analyze the following physicochemical properties: radiopacity, final setting time, calcium release, pH change, solubility, water sorption, porosity, surface morphology, and apatite-forming ability of two calcium silicate-based materials.Material and methodsWe tested MTA Repair HP and MTA Vitalcem in comparison with conventional MTA, analyzing radiopacity and final setting time. Water absorption, interconnected pores and apparent porosity were measured after 24-h immersion in deioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 29 publications
9
54
2
4
Order By: Relevance
“…These data disagree with the present study, where positive structures for von Kossa and polarized light were observed, which would require the release of calcium into the tissue to occur. In addition, according to Guimarães et al (19), the properties of calcium silicate cements that are due to the formation of calcium hydroxide associated with the release of calcium ions, which allow the alkalinizing activity, were observed in both white MTA-Ang and MTA-HP (19).…”
Section: Discussionmentioning
confidence: 99%
“…These data disagree with the present study, where positive structures for von Kossa and polarized light were observed, which would require the release of calcium into the tissue to occur. In addition, according to Guimarães et al (19), the properties of calcium silicate cements that are due to the formation of calcium hydroxide associated with the release of calcium ions, which allow the alkalinizing activity, were observed in both white MTA-Ang and MTA-HP (19).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, supplementary agents as propylene glycol sodium phosphate dibasic or methylcellulose and calcium chloride could well improve significantly different properties of final hydrated material although particular attention to all biocompatibility aspects involved should be taken into consideration . Also, the presence of the plasticizer in MTA Repair HP might increase its solubility and porosity …”
Section: Discussionmentioning
confidence: 99%
“…Eneide et al also showed that antibiofilm efficacy of different irrigation solutions could be increased by various irrigation methods such as passive ultrasonic irrigation (PUI) and passive sonic irrigation (PSI), compared to theconventional needle irrigation technique [ 40 ]. Although a recent literature review reveals that new endodontic cement MTA Repair HP has successful physicochemical and biocompatible properties, such as including a plasticizer to simplify manipulation and insertion to the root canals [ 13 , 14 , 15 ], studies related to the root-end filling/apical sealing performance of MTA Repair HP, as well as to the effects of LAI on both tested calcium silicate cements,are very scarce. Therefore, the possibility of a comparison of the apical microleakage quality of these materials regarding LAI after retrograde filling with similar studies is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The liquid state of this product is obtained by the addition of an organic plasticizer (to gain plasticity and thus increase its manipulation) into distilled water [ 13 , 14 ]. These bioactive materials are mainly recommended for the dental pulp treatments (pulp capping, pulpotomy), apexification, apexogenesis, root-end filling and repair of root canal resorption [ 15 ].…”
Section: Introductionmentioning
confidence: 99%